Clinicopathological characteristics and outcomes of colorectal mucinous adenocarcinoma: a retrospective analysis from China - Huang, An; Yang, Yong; Sun, Zhuang; Hong, Haopeng; Chen, Jiajia; Gao, Zhaoya; Gu, Jin (Frontiers in Oncology, 2024)
Background Mucinous adenocarcinoma (MAC) is a unique subtype of colorectal cancer and its prognostic value remains controversial. This study aimed to compare the clinicopathological characteristics and prognostic differences between patients with MAC and non-mucinous adenocarcinoma (NMAC). Methods 674 patients with NMAC, 110 patients with adenocarcinoma with mucinous component (ACWM) and 77 patients with MAC between 2016-2019 were enrolled in the study. Univariate and multivariate Cox regression were performed to analyze the factors associated with prognosis. Predictive nomograms of overall survival (OS) and cancer-specific survival (CSS) for patients with colorectal adenocarcinoma were constructed. Confounding factors were eliminated by propensity score matching (PSM). Results Compared with patients with NMAC, patients with MAC were more likely to have a tumor located at the proximal colon, present with a larger tumor diameter, more advanced T stage, higher frequency of metastasis, deficiency of mismatch repair, and elevated preoperative carcinoembryonic antigen. Patients with MAC were related to worse OS (HR=2.53, 95%CI 1.73-3.68, p<0.01) and CSS (HR=3.09, 95%CI 2.10-4.57, p<0.01), which persisted after PSM. Subgroup analysis demonstrated that patients with left-sided or stage III/IV MAC exhibited a comparatively worse OS and CSS than those with NMAC. Furthermore, in patients with stage II with a high-risk factor and stage III MAC, adjuvant chemotherapy was associated with an improved OS, CSS, and RFS. Conclusion Compared with the NMAC phenotype, the MAC phenotype was an independent risk factor for poor prognosis in colorectal adenocarcinoma with worse OS and CSS, particularly patients with left-sided colorectal cancer and stage III/IV. However, patients with MAC can still benefit from adjuvant chemotherapy.